Enhancing access of rice farmers to weather-adjusted farm-level agro-advisories for increased climate resilience - Castillo, Roweno; Balanza, Jane Girly; Alvina, Lorenzo; Sartas, Murat; Vila, Jerome; Baradas, Airene Claire; Gutierez, Mary Anne; Raviz, Jeny; Laborte, Alice; Hellin, Jon (International Rice Research Institute, 2024)
Two digital platforms, the Rice Crop Manager Advisory Service (RCMAS) and Agro-climatic Advisory Portal (ACAP), are linked via Applications Programming Interface (API) to provide rice farmers with enhanced weather-adjusted farm-level agro-advisories on crop and nutrient management. The link is called Climate+. The enhanced agro-advisories are sent as short messaging service (SMS) to farmers mobile phone number when there is potential climate risk, based on the weather forecasts, coinciding with the critical growth stages of the rice plant. Interviews and baseline survey with farmers were conducted in 4 pilot villages in Libmanan, Camarines Sur. Sending of the SMS was done across the Bicol Region during wet season 2024. As of October 15, there were 10,717 SMS advisories issued across the Bicol Region, with Minalabac, Camarines Sur receiving the highest number related to potential risk of water shortages and flooding. Validation of Climate+ in Libmanan is yet to be completed by end of November 2024. Baseline and endline data will be used to refine the framework and content of Climate+ before implementation beyond Bicol.